Discours Analysis : A p.ratical Introduction - PATRICIA, CANNING; WALKER (new york : Routledge Taylor and Francis Group., 2024)
Discourse Analysis p.rovides an essential and p.ractical introduction for students studing modules on the analysis of language in use it exp.lores the ways in wich language is used and organised in witten and sp.oken taxts to generate meanings and takes into account the social contexts of p.roduction and the social roles and identities of those involved
index:p..323-325
Keywords: communication; DISCOURSE ANALYSIS